The Effect of the APOE-ε4 Allele on the Cholinergic Circuitry for Subjects With Different Levels of Cognitive Impairment - Lai, Ying-Liang Larry; Chen, Kuan; Lee, Tzu-Wei; Tso, Chao-Wei; Lin, Hui-Hsien; Kuo, Li-Wei; Chen, Cheng-Yu; Liu, Hua-Shan (Frontiers in Neurology, 2021)
Background Cholinergic deficiency has been suggested to associate with the abnormal accumulation of Aβ and tau for patients with Alzheimer’s disease (AD). However, no studies have investigated the effect of APOE-ε4 and group differences in modulating the cholinergic basal forebrain-amygdala network for subjects with different levels of cognitive impairment. We evaluated the effect of APOE-ε4 on the cholinergic structural association and the neurocognitive performance for subjects with different levels of cognitive impairment. Methods We used the structural brain magnetic resonance imaging scans from the Alzheimer’s Disease Neuroimaging Initiative dataset. The study included cognitively normal (CN, n=167) subjects and subjects with significant memory concern (SMC, n=96), early mild cognitive impairment (EMCI, n=146), late cognitive impairment (LMCI, n=138), and AD (n=121). Subjects were further categorized according to the APOE-ε4 allele carrier status. Main effects of APOE-ε4 and group difference on the brain volumetric measurements were assessed. Regression analyses were conducted to evaluate the associations among cholinergic structural changes, APOE-ε4 status, and cognitive performance. Results We found that APOE-ε4 carriers in the disease group showed higher brain atrophy than noncarriers in the cholinergic pathway, while there is no difference between carriers and noncarriers in the CN group. APOE-ε4 allele carriers in the disease groups also exhibited a stronger cholinergic structural correlation than noncarriers did, while there is no difference between the carriers and noncarriers in the CN subjects. Disease subjects exhibited a stronger structural correlation in the cholinergic pathway than CN did. Moreover, APOE-ε4 allele carriers in the disease group exhibited a stronger correlation between the volumetric changes and cognitive performance than noncarriers did, while there is no difference between carriers and noncarriers in CN. Disease subjects exhibited a stronger correlation between the volumetric changes and cognitive performance than CN subjects did. Conclusion Our results confirmed the effect of APOE-ε4 on and group differences in the associations with the cholinergic structural changes that may reflect impaired brain function underlying neurocognitive degeneration in AD.